Ideal Relationship Between Pancasila and Indonesian Muslims - Ahmad Choirul Rofiq (ARISTO, 2020)
After successfully proclaiming the proclamation of independence, the Indonesian people made an agreement to ratify the Pancasila as the basis of the Indonesian nation. The Pancasila values were explored directly from the noble values possessed by the Indonesian people before Indonesian independence. This paper through library research concludes that the Pancasila historically underwent its dynamics since the Old Order government until the Reform Era, especially in its ideological process among plural Indonesian society. The ideology of Pancasila has been confronted with other ideologies, such as communist ideology and Islamic ideology which seeks to create an Indonesian nation in accordance with each ideology. Although the teachings of Islam are not contrast to the Pancasila, but the political movement of some Indonesian Muslims to establish an Islamic state or Khilafah in Indonesia clearly contradicts the spirit of Pancasila because Indonesia is a nation achieved by agreement of all Indonesian people with their various religions. Therefore, the Indonesian Muslims (as well as other non-Muslims) must prove their main role in maintaining the continuity of Pancasila and the unity of Indonesia with its Bhinneka Tunggal Ika. Besides, the Government leaders of Indonesia together with all Indonesian society must practice the holy values of Pancasila, maintain the unitary of the Indonesian nation, and realize a prosperous Indonesia based on the Pancasila.